S129 The natural history of bronchial pre-invasive disease. (14th November 2013) - Brown, JM; Hardavella, G; Carroll, B; Falzon, M; Navani, N; George, PJ; Janes, SM
Abstract : Background: Bronchial pre-invasive lesions represent the earliest stages of the stepwise progression of squamous carcinogenesis, they predominantly affect the large airways and are readily detectable using autofluoresence bronchoscopy (AFB) however very little is known about the natural history of these lesions and no randomised data exists to determine whether intervention before progression to invasion improves outcome. Methods: A total of 94 patients with bronchial dysplasia were enrolled into an on-going surveillance cohort at University College London Hospital running prospectively since 1999. Lesions were biopsied longitudinally and kept under regular surveillance with AFB and low dose annual CT scanning until resolution or progression to invasive disease occurred. Retrospective analysis of lesional destiny was undertaken to determine the proportions of progressive vs. regressive lesions that occur in low grade dysplasia (LGD- squamous metaplasia, mild and moderate dysplasia) vs. high grade dysplasia (HGD- severe dysplasia (SD) and carcinoma-in-situ). A lesion was considered to have progressed/ regressed if it crossed between groups (LGD, HGD, invasive cancer). Results: A total of 117 separate lesions that were biopsied on more than one occasion were identified of which 61 were HGD and 56 LGD. Of the low grade lesions 54/56 (96%) regressed or remained static, 1 (2%) progressed to CIS and 1 (2%) to invasive carcinoma both of these lesions progressed from moderate dysplasia. Of the high grade lesions there were 13 SD and 48 CIS, overall 35/61 (57%) of HGD progressed to invasive cancer 9/61 (15%) regressed and 17/61 (28%) remained static. There was a trend toward higher progression to cancer (62% vs 56%) and lower rates of regression (8% vs. 17%) for SD versus CIS in the HGD cohort although the numbers are too small to be statistically significant (see fig. 1 ). In the HGD group median time to invasion was 9.5 months (range 3–49), static lesions were documented to have remained as such for a median of 17 months (range 4–60). Conclusions: In our cohort we see very few lesions following the traditional stepwise progression and LGD remains relatively indolent. There is a significant proportion of HGD that progresses to invasive cancer and further studies are required to test the role of endobronchial intervention to prevent progression and to determine the most efficacious modality of treatment.